Essentials of research method - Othman Mohd Yunus (Penerbit Universiti Teknologi Mara, 2013)
This book guides readers to every aspect of a research in the right perspective. It is organized in such a way to avoid all discussion from being rhetoric but keeping them brief and straight forward. It provides readers with a comprehensive description of what a research is, its importance, varieties, and the step-by-step research process over several chapters.